2012
DOI: 10.1111/j.1460-2466.2012.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Real-World Beliefs With Controversial Movies: Processes and Mechanisms of Narrative Persuasion

Abstract: Empirical research has found that exposure to specific fictional narratives exerts significant effects on attitudes and beliefs. However, there is little research about the persuasive impact of controversial movies. We present an experimental research study designed to analyze the attitudinal impact of one controversial film (Camino), according to narrative persuasion theoretical models. Because of its critical message toward Opus Dei, this film triggered some controversy in Spain during its release. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 18 publications
6
103
0
19
Order By: Relevance
“…Para definir la identificación con los personajes, Igartua & Páez (1998) propusieron la escala EDI, formada por 17 ítems y que ha sido aplicada y afinada por trabajos posteriores (Igartua & Muñiz, 2008;Igartua, 2010Igartua, , 2012Soto-Sanfiel et al, 2010). Igartua & Páez (1998) caracterizan la identificación como un concepto multidimensional relacionado con una serie de procesos psicológicos: 1. la empatía cognitiva, definida como la capacidad de "comprender o ponerse en el lugar de los protagonistas" (relacionada con la capacidad de adoptar el punto de vista del personaje y seguir la historia desde su perspectiva); 2. la empatía emocional, definida como la posibilidad de "sentir lo que los protagonistas sienten, implicarse afectivamente de forma vicaria o preocuparse por sus problemas" (relacionada con la posibilidad de vivenciar emociones semejantes a las de los personajes); 3. la capacidad de fantasear o imaginar, definida como la capacidad del sujeto para "anticipar las situaciones a las que se expondrían los protagonistas de los relatos de ficción e inferir cuáles serían las consecuencias de las acciones", y 4. el volverse protagonista, definida como la "sensación de sentirse como si uno mismo fuera uno de los protagonistas durante el visionado" (1998, pp.424).…”
Section: La Identificación Con Los Personajesunclassified
See 2 more Smart Citations
“…Para definir la identificación con los personajes, Igartua & Páez (1998) propusieron la escala EDI, formada por 17 ítems y que ha sido aplicada y afinada por trabajos posteriores (Igartua & Muñiz, 2008;Igartua, 2010Igartua, , 2012Soto-Sanfiel et al, 2010). Igartua & Páez (1998) caracterizan la identificación como un concepto multidimensional relacionado con una serie de procesos psicológicos: 1. la empatía cognitiva, definida como la capacidad de "comprender o ponerse en el lugar de los protagonistas" (relacionada con la capacidad de adoptar el punto de vista del personaje y seguir la historia desde su perspectiva); 2. la empatía emocional, definida como la posibilidad de "sentir lo que los protagonistas sienten, implicarse afectivamente de forma vicaria o preocuparse por sus problemas" (relacionada con la posibilidad de vivenciar emociones semejantes a las de los personajes); 3. la capacidad de fantasear o imaginar, definida como la capacidad del sujeto para "anticipar las situaciones a las que se expondrían los protagonistas de los relatos de ficción e inferir cuáles serían las consecuencias de las acciones", y 4. el volverse protagonista, definida como la "sensación de sentirse como si uno mismo fuera uno de los protagonistas durante el visionado" (1998, pp.424).…”
Section: La Identificación Con Los Personajesunclassified
“…Específicamente, este estudio explora la identificación con los personajes, una variable que, en la psicología de los medios, se considera central para comprender los efectos del entretenimiento (Cohen, 2006;Igartua, 2012), porque explica respuestas generales a las ficciones, como el disfrute (Igartua, 2012) Como se ha avanzado, los resultados de esta investigación son coherentes con trabajos previos sobre identificación con los personajes. En general, confirman que las características particulares de las audiencias influyen en la identificación.…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…In the field of narrative persuasion, it has been shown that identification with characters plays an important mediating role: For a narrative to cause a persuasive impact there must be a high identification with the characters involved (de Graaf et al, 2012;Hoeken & Fikkers, 2014;Igartua & Barrios, 2012;Igartua & Vega, 2016). In this context, identification with characters is a cognitive-affective process that takes place during reception (reading, viewing) of the narrative message, and that is linked to perspective-taking or cognitive empathy (putting oneself in the shoes of the character), emotional empathy (feeling the same emotions as the character), and the temporary loss of self-awareness (the receiver of the narrative imagines being the character, taking on his or her identity, and becoming merged with the character) (Cohen, 2001;Igartua & Barrios, 2012;Moyer-Gusé, 2008).…”
Section: Similarity Identification With Characters and Persuasive Imentioning
confidence: 99%
“…A narrative always provides information (and implicit or explicit arguments) based on which individuals can change or adapt their beliefs, attitudes and behaviors. Research into narrative persuasion studies the processes or mechanisms that explain how narratives can change attitudes, beliefs or behaviors (de Graaf, Hoeken, Sanders, & Beentjes, 2012;Green & Brock, 2000;Hoeken & Fikkers, 2014;Igartua & Barrios, 2012). A meta-analysis review has shown that narratives have significant effects on attitudes, beliefs, behavioral intention and behavior (Braddock & Dillard, 2016).…”
Section: Introductionmentioning
confidence: 99%